Postural instability in children with severe inner ear malformations: Characteristics of vestibular and balance function. (1st February 2021) - Ertugrul, Gorkem; Sennaroglu, Gonca; Karakaya, Jale; Sennaroglu, Levent
Abstract: Objective: To investigate the postural instability and vestibular functions in children with severe inner ear malformations (IEMs). Design: A prospective case-control study. Study sample: The study group consisted of 10 children using unilateral auditory brainstem implant (ABI) with labyrinthine aplasia or rudimentary otocyst. The age-matched control groups consisted of 10 unilateral cochlear implant (CI) users with normal inner ear structures and 10 healthy peers. All tests were performed to implant users when the implants were off. Results: All median VOR gains in the ABI group (median anterior, lateral, and posterior canal 0.15, 0.05, and 0.05, respectively, for the non-implanted sides) were significantly lower than those of the control groups (median VOR gains ≥ 0.90 in both control groups). There were no oVEMP and cVEMP responses in the study group. The mean BOT-2 balance scores of the ABI (3.70 ± 1.34) group was dramatically lower than those of the CI (9.40 ± 2.88) and healthy control (16.20 ± 4.16, p < 0.001). Conclusions: The postural instability in children with severe IEMs was higher than those in CI users with normal inner ear structures and healthy peers. The level of deficiency in the labyrinthine was more important for postural stability in children.